Engineering of l-threonine and l-proline biosensors by directed evolution of transcriptional regulator SerR and application for high-throughput screening - Wei Pu; Jinhui Feng; Jiuzhou Chen; Jiao Liu; Xuan Guo; Lixian Wang; Xiaojia Zhao; Ningyun Cai; Wenjuan Zhou; Yu Wang; Ping Zheng; Jibin Sun (Bioresources and Bioprocessing)
Abstract Amino acids are important bio-based products with a multi-billion-dollar market. The development of efficient high-throughput screening technologies utilizing biosensors is essential for the rapid identification of high-performance amino acid producers. However, there remains a pressing need for biosensors that specifically target certain critical amino acids, such as l-threonine and l-proline. In this study, a novel transcriptional regulator-based biosensor for l-threonine and l-proline was successfully developed, inspired by our new finding that SerE can export l-proline in addition to the previously known l-threonine and l-serine. Through directed evolution of SerR (the corresponding transcriptional regulator of SerE), the mutant SerRF104I which can recognize both l-threonine and l-proline as effectors and effectively distinguish strains with varying production levels was identified. Subsequently, the SerRF104I-based biosensor was employed for high-throughput screening of the superior enzyme mutants of l-homoserine dehydrogenase and γ-glutamyl kinase, which are critical enzymes in the biosynthesis of l-threonine and l-proline, respectively. A total of 25 and 13 novel mutants that increased the titers of l-threonine and l-proline by over 10% were successfully identified. Notably, six of the newly identified mutants exhibited similarities to the most effective mutants reported to date, indicating the promising application potential of the SerRF104I-based biosensor. This study illustrates an effective strategy for the development of transcriptional regulator-based biosensors for amino acids and other chemical compounds.